312. Unplanned Readmission after Hospitalization with Staphylococcus aureus Bacteremia in Children: a Multistate Population Based Study. (31st December 2020) - Inagaki, Kengo; Ansari, Md Abu Yusuf; Hobbs, Charlotte V
Abstract: Background: Staphylococcus aureus bacteremia is associated with substantial mortality and morbidity. Readmission is becoming increasingly recognized as an important quality measure and can inform optimal patient care. We previously reported readmission analyses in the setting of S. aureus bacteremia in the adult population. However, readmission has not been characterized in children. Methods: We performed a population-based longitudinal observational study using the State Inpatient Database from New York, Florida, and Washington states, 2009–2015. Children aged 18 years or younger hospitalized with S. aureus bacteremia were included. The outcome of unplanned readmission within 30 days and 90 days of discharge was assessed by developing Cox proportional hazards regression models. Results: Of 1240 children that were included in the analysis, 18% (223 children) had unplanned readmission within 30 days after discharge, and 28.3% were readmitted within 90 days. On multivariable analysis, children with underlying conditions of hematologic malignancy (hazard ratio, HR: 1.67, 95% confidence interval, CI: 1.09–2.56) and catheter related infection (HR: 1.79, 95%CI: 1.31–2.45) had higher hazards of readmission, whereas coexisting skin and soft tissue infection (HR: 0.42, 95%CI: 0.24–0.71) was associated with a lower rate of readmission (Table, Figure). In addition to these, solid tumor malignancy and longer length of stay during the original hospitalization were associated with higher hazards of 90-day readmission. The median cost of the original hospitalization for S. aureus bacteremia was 29914 (interquartile range, IQR: 13276-71284), and that of 30-day readmission was 10956 (interquartile range, IQR: 5765-24753). Table Figure Conclusion: Unplanned readmission is common and costly among children who survived S. aureus bacteremia, occurring in 18% and 28.3% within 30 and 90 days after discharge, respectively. Those with malignancies and catheter related infection had higher hazards of unplanned readmission. Further research is needed to identify optimal interventions to reduce readmission rates associate with S. aureus bacteremia in children. Disclosures: All Authors : No reported disclosures